Base erosion and profit shifting : the effectiveness of imposing fixed ratio limitation rules as a means of combatting excessive interest deductions - Oguttu, Annet Wanyana (University of Pretoria, 2020)
Mini Dissertation (MCom)--University of Pretoria, 2019.